Achieve safety for workers in times of pandemics (Analytical Sharia Study) - Al-Jabour, Fadi (Jordan Journal of Islamic Studies, 2023)
This study discusses an important emerging issue, as it shows the impact of pandemics on employee contracts, It provides legitimate solutions and measures for workers whose contracts have been broken, and for workers whose source of income has ceased. The study used the inductive, descriptive and analytical method, and concluded that Islamic law showed how to deal with work contracts under emergency and force majeure conditions, and that it provided a number of legitimate measures that guarantee the future of workers when it is impossible for their contracts to continue or their source of income is interrupted, and the study concluded with some recommendations.